IMPLIKASI BANTUAN IMF DAN WORLD BANK TERHADAP KEMISKINAN STRUKTURAL DI SOMALIA - Ersa Dwi Yulianda (HI 16 UMY, 2016)
This Journal will explained about IMF and World Bank program has led the Somali economy into a vicious circle, reduced livestock encourage nomadic herders become starved to death, which in turn impact on grain producers are difficult to sell, so the only choice is sold or bartered their grain to feed livestock. Traditional social structure and economy destroyed. The fall of foreign exchange earnings from declining cattle exports and remittances (from Somali workers in the gulf states) impact on the balance of payments and the state of public finances that lead to damage to the economic and social programs of the government.Which in turn, the Structural Adjustment Program destroy somalia and pushing somalia to a failed state.